Antibiotic Treatment Shapes the Antigenic Environment During Chronic TB Infection, Offering Novel Targets for Therapeutic Vaccination - Chuang, Yu-Min; Dutta, Noton K.; Gordy, James T.; Campodónico, Victoria L.; Pinn, Michael L.; Markham, Richard B.; Hung, Chien-Fu; Karakousis, Petros C. (Frontiers in Immunology, 2020)
The lengthy and complicated current regimen required to treat drug-susceptible tuberculosis (TB) reflects the ability of Mycobacterium tuberculosis (Mtb) to persist in host tissues. The stringent response pathway, governed by the dual (p)ppGpp synthetase/hydrolase, RelMtb, is a major mechanism underlying Mtb persistence and antibiotic tolerance. In the current study, we addressed the hypothesis that RelMtb is a “persistence antigen” presented during TB chemotherapy and that enhanced immunity to RelMtb can enhance the tuberculocidal activity of the first-line anti-TB drug, isoniazid, which has reduced efficacy against Mtb persisters. C57BL/6 mice and Hartley guinea pigs were aerosol-infected with Mycobacterium tuberculosis (Mtb) and, 4 weeks later, received either human-equivalent daily doses of isoniazid alone, or isoniazid in combination with a DNA vaccine targeting relMtb. After isoniazid treatment, there was a significant reduction in dominant antigen ESAT6-specific CD4+ or TB10.4-specific CD8+ T cells in the lungs and spleens of mice. However, the total number of RelMtb-specific CD4+ T cells remained stable in mouse lungs and spleens, as did the number of RelMtb-specific CD8+T cells. Therapeutic vaccination with relMtb DNA vaccine enhanced the activity of isoniazid in Mtb-infected C57BL/6 mice and guinea pigs. When treatment with isoniazid was discontinued, mice immunized with the relMtb DNA vaccine showed a lower mean lung bacterial burden at relapse compared to the control group. Our work shows that antitubercular treatment shapes the antigenic environment, and that therapeutic vaccination targeting the Mtb stringent response may represent a novel approach to enhance immunity against Mtb persisters, with the ultimate goal of shortening curative TB treatment.